2014
DOI: 10.1021/pr401081b
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS Proteomics Analysis of the Insulin/IGF-1-DeficientCaenorhabditis elegans daf-2(e1370)Mutant Reveals Extensive Restructuring of Intermediary Metabolism

Abstract: The insulin/IGF-1 receptor is a major known determinant of dauer formation, stress resistance, longevity, and metabolism in Caenorhabditis elegans. In the past, whole-genome transcript profiling was used extensively to study differential gene expression in response to reduced insulin/IGF-1 signaling, including the expression levels of metabolism-associated genes. Taking advantage of the recent developments in quantitative liquid chromatography mass spectrometry (LC–MS)-based proteomics, we profiled the proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 161 publications
(421 reference statements)
3
86
2
Order By: Relevance
“…With the dawn of the omics era, transcriptomic (McElwee et al, 2003;Murphy et al, 2003;McElwee et al, 2004;Halaschek-Wiener et al, 2005), proteomic (Dong et al, 2007;Jones et al, 2010;Depuydt et al, 2013Depuydt et al, , 2014Stout et al, 2013;Walther et al, 2015) and metabolomic (Fuchs et al, 2010) studies showed that IIS mutants undergo massive changes in gene expression and shifts in metabolic networks. DAF-16 targets were also determined by analysing DNA binding sites of this transcription factor with DamID and ChIP (Oh et al, 2006;Schuster et al, 2010).…”
Section: The Foxo/daf-16 Lifespan Programmentioning
confidence: 99%
See 4 more Smart Citations
“…With the dawn of the omics era, transcriptomic (McElwee et al, 2003;Murphy et al, 2003;McElwee et al, 2004;Halaschek-Wiener et al, 2005), proteomic (Dong et al, 2007;Jones et al, 2010;Depuydt et al, 2013Depuydt et al, , 2014Stout et al, 2013;Walther et al, 2015) and metabolomic (Fuchs et al, 2010) studies showed that IIS mutants undergo massive changes in gene expression and shifts in metabolic networks. DAF-16 targets were also determined by analysing DNA binding sites of this transcription factor with DamID and ChIP (Oh et al, 2006;Schuster et al, 2010).…”
Section: The Foxo/daf-16 Lifespan Programmentioning
confidence: 99%
“…The morphology of IIS mutants may provide a first clue: daf-2 mutants tend to accumulate large amounts of fat (Ogg et al, 1997;Depuydt et al, 2014) and glycogen (Frazier & Roth, 2009;Depuydt et al, 2014) in the intestine, hypodermis and to some extent in the body wall muscles, thereby phenocopying dauers (Fig. 2).…”
Section: Investment In Fat and Glycogen Synthesismentioning
confidence: 99%
See 3 more Smart Citations